2022
DOI: 10.1371/journal.pone.0254302
|View full text |Cite
|
Sign up to set email alerts
|

Auditory and sexual preferences for a father’s song can co-emerge in female Bengalese finches

Abstract: Birdsong is an important communication signal used in mate choice. In some songbird species, only the males produce songs. While the females of those species do not sing, they are sensitive to inter- and intra-species song variations, and the song preferences of females depend on their developmental experiences and/or genetic predispositions. For example, in Bengalese finches and zebra finches, adult females prefer the song to which they were exposed early in life, such as the father’s song. In the current stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 53 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…As this would not always be very practical, an alternative way is to examine the correlation between behavioral indices in laboratory experiments. As such, in a series of studies of female Bengalese finches, the response rate of a specific call type was positively correlated with CSDs as well as with phonotaxis at an individual or a population level ( Kato et al, 2010 ; Dunning et al, 2014 ; Fujii et al, 2021 ; Fujii and Okanoya, 2022 ). Because using multiple behavioral tests to measure subjects within a single study can be logistically challenging, the most practical approach may be to gradually accumulate the results from an entire research community over time.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…As this would not always be very practical, an alternative way is to examine the correlation between behavioral indices in laboratory experiments. As such, in a series of studies of female Bengalese finches, the response rate of a specific call type was positively correlated with CSDs as well as with phonotaxis at an individual or a population level ( Kato et al, 2010 ; Dunning et al, 2014 ; Fujii et al, 2021 ; Fujii and Okanoya, 2022 ). Because using multiple behavioral tests to measure subjects within a single study can be logistically challenging, the most practical approach may be to gradually accumulate the results from an entire research community over time.…”
Section: Discussionmentioning
confidence: 93%
“…For instance, in the studies on Bengalese finches from our laboratories, we found that while some song features are preferred by majority of females, there are also substantial individual differences in the song preference ( Morisaka et al, 2008 ; Kato et al, 2010 ; Dunning et al, 2014 , 2020 ). Other studies provide a possibility that the source of individual variation lies in the early-life experience of father’s song ( Fujii et al, 2021 ; Fujii and Okanoya, 2022 ). As the Bengalese finch song is particularly interesting for the sequential complexity and its evolutionary change through domestication process ( Okanoya, 2004a ; Okanoya, 2004b ), scrutinizing the universality and individual differences of female song preference from the perspectives of neural mechanisms and development potentially help investigate the function and evolution of the sequential complexity, and vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For all behaviours measured, the direction of effect was towards a stronger response to familiar non-father songs compared to unfamiliar songs.. A wide range of song features, including song and note structure, are socially inherited in this species (Lewis et al, 2021a), meaning that song type and song similarity likely indicate that birds are (socially) related. There is some evidence for generalization of preference from other Estrildid finch species, with birds showing greater responses to songs that were more similar to those of their father (Fujii and Okanoya, 2022; Miller, 1979; Wei et al, 2022). However, this is not the case in all studies.…”
Section: Discussionmentioning
confidence: 99%